PERAN PEREMPUAN PEDAGANG KAKI LIMA DALAM MENINGKATKAN EKONOMI KELUARGA SEBELUM DAN SEMASA PANDEMI COVID-19 DI KOTA BANDA ACEH - Faisul Siddiq; Fikriah Fikriah (Fakultas Ekonomi dan Bisnis UNSYIAH, 2022)
AbstractThis study aims to determine the role of women street vendors in improving the family economy before and during the covid-19 pandemic in Banda Aceh City and to determine the different roles of women street vendors in improving the family economy before and during the covid-19 pandemic in Banda Aceh City. The variables in this study include the income of street vendors, types of merchandise, means of transportation, capital, age, education, business location and working hours of female street vendors. the author uses a quantitative descriptive approach. The results showed that vulnerable workers in Pidie Regency who received assistance had more of the role of women Street Vendors in Improving the Family Economy Before and During the Covid-19 Pandemic in Banda Aceh City. During the Covid-19 pandemic, the influencing variables are capital and transportation access. The results of the chi Square test analysis show that there are significant differences in the role of women street vendors in improving the family economy before and during the Covid-19 pandemic in Banda Aceh City. Furthermore, it is hoped that street vendors (PKL) can continue to sell and pay more attention to health risks related to the Covid-19 virus, obey the health protocols from the government, in order to stop the wave of spreading the Covid-19 virus, because if you don't, your family is also at risk of contracting the virus. and for the government to provide special stalls for women street vendors so that they can sell comfortably and sustainably to help improve the family's economy.Keywords: Income, female street vendors, covid, pandemic